2020
DOI: 10.1177/0165025420965731
|View full text |Cite
|
Sign up to set email alerts
|

Family socioeconomic status and parental expectations affect mathematics achievement in a national sample of Chilean students

Abstract: Family socioeconomic status (SES) has a significant influence on children’s academic success and is related to parents’ attitudes toward education. Moreover, according to the expectancy-value theory, parental expectations are linked to their children’s perceptions of school, which, in turn, influences the way their children invest themselves in education. In this study, we aimed to test a part of the theorical expectancy-value family socialization model that links family SES and parental expectations and explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 32 publications
(91 reference statements)
3
30
1
Order By: Relevance
“…Unexpectedly, family SES was not associated with the test scores, which is inconsistent with many previous studies (e.g., Hascoet et al, 2021; Zhang et al, 2020). However, this result may be unreliable despite the large sample.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unexpectedly, family SES was not associated with the test scores, which is inconsistent with many previous studies (e.g., Hascoet et al, 2021; Zhang et al, 2020). However, this result may be unreliable despite the large sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, the current sample came from the same middle school, which means that the range of family SES in this study is probably not representative of the population. The studies that found positive associations between family SES and academic achievement collected data from several schools from different cities (Hascoet et al, 2021; Zhang et al, 2020). Meanwhile, we found that one study collected data from one school and showed that family SES was weakly correlated with test scores ( p = .05) (Ren et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that their results varied somewhat across cultures. Drawing on Eccles' expectancy-value theory, Hascoët et al (2021) examined the effects of parents' expectations and found attitudes as an expression of expectations, mediating the effects that underlying expectations have on parenting and, in turn, on outcomes. They also established a link between parental attitudes and children's positive self-concept.…”
Section: Parental Attitudesmentioning
confidence: 99%